Clusterin serum levels are elevated in patients with early rheumatoid arthritis and predict disease activity and treatment response - Kropáčková, Tereza (Sci Rep, 2021)
Clusterin (CLU) is a molecular chaperone that participates in a variety of biological processes. Recent studies indicate its possible involvement in the development of bone erosions and autoimmunity. The aim of this study was to investigate its serum concentrations in patients with early rheumatoid arthritis (RA) and to explore their potential relationship with disease activity and treatment response. Serum levels of CLU were measured in 52 patients before and 3 months after the initiation of treatment and in 52 healthy individuals. CLU levels at baseline were significantly increased in patients with early RA compared with healthy subjects (p < 0.0001). After 3 months of treatment, the levels of CLU decreased and reached concentrations comparable to those in controls. Even though there was no relationship between CLU levels and disease activity at baseline, CLU levels positively correlated with disease activity at months 3, 6 and 12 after treatment initiation. Using ROC analysis, lower CLU baseline levels predicted achieving the therapeutic target of low disease activity and remission at months 3, 6 and 12. In summary, we found increased serum concentrations of clusterin in treatment-naïve patients with early rheumatoid arthritis, and we suggest clusterin as a predictive biomarker of disease activity and treatment response.